Inovasi Layanan Mobil Siaga Desa dalam Meningkatkan Pelayanan Publik di Kabupaten Bojonegoro - Riyani, Septia Dwi; Septian, Esa; Suhindarno, Heny (LPPM Institut Nasional Laa Roiba Bogor, 2024)
The Bojonegoro Regency Government, through the Social Service, provides innovative Village Alert Car services to improve public services to village communities in Bojonegoro Regency. This innovation will be implemented in December 2022 as a service product innovation. This research aims to determine and describe the innovation of the Village Alert Car service. This research uses descriptive qualitative research with data collection techniques in the form of interviews, observation and documentation. Researchers use the Typology of Innovation theory according to Mulgan & Albury in Muluk (2008), an innovation is said to be successful if the innovation is the result of the creation and implementation of product innovation, process innovation, method innovation, strategy or policy innovation, and system innovation. Based on this theory, the research results show that currently the Bojonegoro Regency Government has provided a safe and comfortable transportation model for village communities in the form of village standby cars. Apart from being easy to use, this transportation has no fees. It is hoped that the innovation of the village standby car service in Bojonegoro Regency will become a role model for other regions in meeting the needs of public facilities for village communities experiencing social emergencies. Although there are several obstacles that must be evaluated based on strategy or policy innovation, namely the outreach carried out by the village government must be improved further, because not all levels of society know about the village standby car policy or program. Even though there are complaints, it is not an obstacle in implementing the village standby car service and it continues to run.